Identity of the spanish reporters, between the ideal and reality. Analisys of parliamentary interventions in 1994 and 2004 - Suárez Villegas, Juan Carlos; Jiménez, Eva (Anàlisi, 2012)
This paper explores the conception of Spanish journalist on journalist identity, from two perspectives: the normative,meaning ideal o ethical view, and the empirical, referred to the reality of the professional practice. In order to compare both perspectives, the authors explore the speeches of journalists in the Congress of Deputies during the debate of three bills, two of them in the legislature 1993-1996 and one in the period of 2004-2008. The results show that journalist adopt two roles: the difusser, from the regulatory perspective, and the journalist in the service of the company, from the empirical perspective. There are not significant differences in the contributions made by the journalists in these two different periods. The authors conclude that journalist identity is still debated and largely questioned by journalist themselves. Additionally, they propose some measures for improving the professional organizations.